Advancing responses to climate change through improved interplay between planning theory and practice. Issue 1 (2nd January 2021) - Matthews, Tony; Baker, Douglas
ABSTRACT: Many planning agencies worldwide now see climate change response as unavoidable. This paper proposes that a central task for contemporary planning theory is to guide planning practice as it develops multi-dimensional responses. We examine three theoretical constructs: anticipatory governance, legitimacy and social-ecological resilience. We argue that each conceptualises challenges climate change presents to planning practice, while providing theoretically informed options for responses. Building on this, we utilize Friedmann's [2008. "The Uses of Planning Theory: A Bibliographic Essay." Journal of Planning Education and Research 28 (2): 247–257. doi:10.1177/0739456X08325220] tasks for planning theory as a framework to assess the utility of planning theories to guide climate change response through practice. Associated issues are discussed, including the influence of translatable planning theories and the value of importing knowledge from other disciplines. The paper concludes that more sophisticated interplay between planning theory and practice may improve planning responses to the climate change threat. The need for planning theory to translate its conceptual discoveries to the domain of practice is key.